Polling sebagai Ekspresi Opini Publik, Pilar Kelima Demokrasi? - Adiputra, Wisnu Martha (Jurnal Ilmu Sosial dan Ilmu Politik, 2008)
Public opinion is one of important elements of democracy. Public opinion is considered as fifth estate of democracy. This paper examines public opinion concept and its position as fifth estate of democracy. It also tries to explore the challenges of public opinion as important factor for democratic political communication in Indonesia. It argues that the absence of public in political communication makes public opinion uneasy to become the fifth estate. This paper acknowledges the importance of public opinion in Indonesian democracy. Moreover, this paper explains how far public opinion draws Indonesian democracy.